Peroxo Species Formed in the Bulk of Silicate Cathodes. Issue 18 (24th March 2021) - Chen, Zhenlian; Schwarz, Bjoern; Zhang, Xianhui; Du, Wenqiang; Zheng, Lirong; Tian, Ailing; Zhang, Ying; Zhang, Zhiyong; Zeng, Xiao Cheng; Zhang, Zhifeng; Huai, Liyuan; Wu, Jinlei; et al.
Abstract: Oxygen redox in Li‐rich oxides may boost the energy density of lithium‐ion batteries by incorporating oxygen chemistry in solid cathodes. However, oxygen redox in the bulk usually entangles with voltage hysteresis and oxygen release, resulting in a prolonged controversy in literature on oxygen transformation. Here, we report spectroscopic evidence of peroxo species formed and confined in silicate cathodes amid oxygen redox at high voltage, accompanied by Co 2+ /Co 3+ redox dominant at low voltage. First‐principles calculations reveal that localized electrons on dangling oxygen drive the O‐O dimerization. The covalence between the binding cation and the O‐O dimer determines the degree of electron transfer in oxygen transformation. Dimerization induces irreversible structural distortion and slow kinetics. But peroxo formation can minimize the voltage drop and volume expansion in cumulative cationic and anionic redox. These findings offer insights into oxygen redox in the bulk for the rational design of high‐energy‐density cathodes. Abstract : Peroxo moieties formed in the bulk of carbon‐coated Mn‐doped Li2 CoSiO4 are characterized by concurrent signatures in the form of an O‐K pre‐edge peak (XAS) and a peroxo O–O stretching mode (Raman). Peroxo formation proves to be a reversible oxygen redox mechanism for the development of high‐energy‐density cathodes in real‐world battery applications.